Internalisasi Kurikulum Pendidikan Agama Islam dalam Penguatan Pendidikan Karakter Berbasis Neurosains - Us’an; Muzayyim Luthfie; Suroto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to gain a deeper understanding of the internalization of the Islamic religious education curriculum in shaping student character in schools. The background to this research stems from the finding that negative behaviors such as brawls, drug cases, bullying, children in trouble with the law, and other criminal acts are still common, even among students who are still in school. This study used library research methods (library research) namely collecting various literature related to curriculum, character education, and neuroscience such as books, journals and discussions relevant to the topic of discussion. Data analysis was conducted using the content analysis method, namely identifying, classifying, and interpreting the free nutritious meals that influence student intelligence. The results of the study indicate that quality education is education that is able to shape the character of its students. This can be done by internalizing the Islamic religious curriculum with neuroscience-based education. The reason is that changing character begins with changing the student's brain. This study recommends to policymakers that character education must be a top priority, and the need for synergy between schools, the government, and parents to ensure the success of this character education.